Analisis Perancangan Strategi Pemasaran Menggunakan Metode SWOT Dan QSPM Di UMKM Pempek Lenlin - Fadly Hanafi; Muhammad Rizki; Nofirza Nofirza; Ismu Kusumanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Starting from the problems experienced by Len-Lin’s Pempek business, where sales did not reach the set targets and did not have a good marketing strategy plan to increase sales. This research was conducted with the aim of formulating a marketing strategy for these SMEs with the SWOT and QSPM methods. This type of research uses descriptive qualitative methods with analysis of Business Development Strategies using EFE and IFE matrices, IE matrices, SWOT matrices and QSPM. The results of this study are in an intermediate position in utilizing internal and external factors for business development with a total IFE of 2.961 and a total of EFE of 2.919. The IE matrix mapping shows that Len-Lin’s Pempek business use the defensive and maintain strategy. From the research results, there are seven alternative strategies that can be used to increase sales or develop a business.